A Conceptual Model of the Healthy Acoustic Environment: Elements, Framework, and Definition - Chen, Jing; Ma, Hui (Frontiers in Psychology, 2020)
Noise has been proved to be a risk factor of physiological and psychological health. Therefore, creating a high-quality acoustic environment for people is particularly important. The aims of this study are to explore the basic elements, propose a conceptual framework, and identify the definition of a healthy acoustic environment. Through the method of grounded theory, 75 respondents participated in interviews. The results revealed that 1) “sound sources and acoustic environment,” “people’s demands,” “criteria and standards of a healthy acoustic environment,” “matching process,” “secondary fitting process,” “context,” and “acoustic environment quality” are the basic elements of a healthy acoustic environment; 2) “Matching process” and “secondary fitting process” connect all the other categories and reflect the processes by which a healthy acoustic environment is judged; 3) Based on the associations revealed in the framework, a healthy acoustic environment is defined as a supportive acoustic environment that can match people’s physiological, psychological, and behavioral demands in context, and that also fits the criteria and standards. The proposal of a conceptual model for a healthy acoustic environment can provide a new perspective on designing and establishing a high-quality acoustic environment required by people in the near future.